Systematic Literature Review: Model Kepemimpinan Holistik : Integrasi Kepemimpinan, Kepengikutan, Tri Hita Karana, dan Pengendalian Pikiran Berbasis Spiritual - Chelsea Mery Andrea Sinambela; Chris Steven Sado Fodhe Au; I Wayan Putra Yasa (KOLONI, 2026)
This study aims to examine and synthesize various scientific literature on leadership and followership, the concept of Tri Hita Karana in self-leadership, and spiritually based mind-control leadership. The method used is a literature review of more than ten relevant scholarly articles from both national and international journals. The findings indicate that leadership and followership have a reciprocal and interdependent relationship in achieving common goals. Furthermore, the concept of Tri Hita Karana provides a value framework emphasizing the balance of human relationships with God (parahyangan), with others (pawongan), and with the environment (palemahan), which plays a crucial role in shaping self-leadership. In addition, spiritual leadership highlights the importance of mind control, self-awareness, and moral values as the core of effective leadership. The integration of these three concepts results in a holistic, ethical, and sustainable leadership model, where self-control serves as the fundamental basis for leading oneself and others. Therefore, the development of leadership that integrates rational, social, and spiritual aspects is essential in addressing the dynamics of modern life.